Treatment Challenges in Acute Minor Ischemic Stroke - Slawski, Diana; Heit, Jeremy J. (Frontiers in Neurology, 2021)
Patients with acute ischemic stroke may present with minor neurologic deficits. Acute treatment decisions depend on the disability imposed by the symptoms along with radiographic features. The presence of disabling neurologic deficits warrants intravenous thrombolysis, but the indications for endovascular therapy are less defined. The degree of disability, presence of a large vessel occlusion with perfusion mismatch, and collateral circulation status may all be factors in selecting patients for endovascular treatment. Identification of patients who are at risk for neurologic deterioration is critical to preventing poor outcomes in this patient population.